Editorial Vol.4(1) (Rupandehi Campus Journal, 2024)
The journal covers a wide range of multidisciplinary topics, including language, literature, mathematics, teaching and learning activities, health, management, law, Buddhism, and social sciences. Going beyond typical academic limits, it investigates ethical and social challenges in health and allied subjects, demonstrating a comprehensive approach to study.In essence, the Rupandehi Campus Journal serves as a vibrant hub where several academic disciplines intersect, encouraging intellectual growth and collaboration. The transition to a biannual publication schedule represents a forward-thinking strategy for keeping the journal at the fore front of intellectual interaction and knowledge sharing.